2009
DOI: 10.1111/j.1460-9568.2009.06655.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma activity and reactivity in human thalamic local field potentials

Abstract: Depth recordings in patients with Parkinson's disease on dopaminergic therapy have revealed a tendency for oscillatory activity in the basal ganglia that is sharply tuned to frequencies of approximately 70 Hz and increases with voluntary movement. It is unclear whether this activity is essentially physiological and whether it might be involved in arousal processes. Here we demonstrate an oscillatory activity with similar spectral characteristics and motor reactivity in the human thalamus. Depth signals were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
63
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 57 publications
8
63
1
Order By: Relevance
“…Finely tuned gamma oscillations in the range of 60-90 Hz are a consistent feature of basal ganglia and thalamic recordings (47) that are diminished in PD patients in the absence of dopaminergic replacement (17,18). However, rather than an increase in finely tuned gamma, here we observed a broader-band gamma power increase, which may represent a general increase in neuronal activity (26).…”
Section: M1 Superficialsupporting
confidence: 81%
See 4 more Smart Citations
“…Finely tuned gamma oscillations in the range of 60-90 Hz are a consistent feature of basal ganglia and thalamic recordings (47) that are diminished in PD patients in the absence of dopaminergic replacement (17,18). However, rather than an increase in finely tuned gamma, here we observed a broader-band gamma power increase, which may represent a general increase in neuronal activity (26).…”
Section: M1 Superficialsupporting
confidence: 81%
“…To further evaluate the changes at specific frequency bands, we calculated the normalized spectrum before, during, and after laser stimulation. We found that optogenetic stimulation of SChIs robustly increased oscillation power across higher frequency bands conventionally defined as alpha (8)(9)(10)(11)(12)(13)(14)(15), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), low gamma (30-60 Hz), and high gamma (60-100 Hz), but not lower frequency bands of delta (1-4 Hz) or theta (4-8 Hz) (Fig. 2 E and F; n = 7 mice).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations